Sistem Informasi Tabungan Siswa Pada SD Dwi Warna Panjang - Chyntia Yuni Arta; Temi Ardiansah (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2023)
SD Dwi Warna is one of the elementary schools in the Bandar Lampung area, the process of processing student savings data is still done manually, recording and storing the data is written in report books and student savings books, and the calculations are still done conventionally using calculators and tools. Data is stored in archive form. The system development method uses extreme programming methods and system design uses UML. So that this research is not subjective, the author also used research methods in the form of observation, literature review and interviews. This system will be tested using ISO 25010 testing. The results achieved are an online-based student savings information system. It is hoped that with the system built, it is hoped that the system built will aim to help make processing student savings data easier. Providing complete information regarding the amount of student savings that have been made and assisting schools in reporting student savings. The results of the ISO 25010 test which was carried out involving 10 respondents showed that the conclusion of the quality of software suitability with an overall score of 90.59% was on a scale of Very Good.